Oxide, Sulphide and Platinum Mineralogy of the South Kawishiwi and Partridge River Intrusions of the Duluth Layered Intrusion Complex Minnesota, U.S.A. - Komppa, Ulla (University of Minnesota Duluth, 1998)
The Duluth Complex in north-east Minnesota, U.S.A., is one of the largest basic layered intrusion complexes in the world, occupying an area of about 4700 km2 • It is composed of several separate intrusions which discharged via the Midcontinent Rift System about 1100 ± 15 Ma ago. Characteristic of the complex is the occurrence of mineralizations containing Cr-Fe-Ti-V oxides, CuNi sulphides and platinum group elements in the troctolitic South Kawishiwi and Partridge River Intrusions on its western and northern edges. The purpose of this work is to study and compare these two adjacent intrusions in terms of their platinum mineralogy and to provide the basic data necessary for determining the origins of their mineralizations. As the platinum mineralizations are closely connected with oxide and sulphide mineralizations, the latter are also examined in detail. The work is based to a great extent on the available literature and on a set of 221 core samples taken from the two intrusions. A total of 119 whole rock x-ray fluorescence analyses, 253 WDS x-ray microanalyses, 68 EDS analyses and 499 scanning electron microscope analyses ( also employing the EDS method) were performed on these cores for the determination of oxides, sulphides and platinum group minerals. The mineralizations of the Duluth Layered Intrusion Complex resemble other corresponding ones in Cu and Ni-bearing basic igneous rocks in their ore mineralogy and in the rock types present. The mineralizations exhibit properties suggestive of a role for both magmatic and hydrothermal processes in the distribution of platinum group elements. The results obtained here are consistent with earlier findings.
Natural Resources Research Institute Report of Investigations
Komppa, UE. 1998. Oxide, sulphide and platinum mineralogy of the South Kawishiwi and Partridge River Intrusions of the Duluth Layered Intrusion Complex, Minnesota, US.A. Dissertation for the degree of Master of Science in geology and mineralogy (no. 772668), presented to the Department of Geosciences, University of Oulu. 104 pp., 21 illustrations, 8 tables and 8 appendices. English Translation by Malcolm Hicks, 2000. Report of Investigation, NRRI/RI-2002/02, January 2002
Keywords: Platinum mineralogy; Oxide mineralizations; Sulphide mineralizations; Duluth Layered Intrusion Complex, Minnesota; Northeast Minnesota; South Kawishiwi Intrusions; Partridge River Intrusions; Midcontinent Rift System; Natural Resources Research Institute; University of Minnesota Duluth